2000
DOI: 10.1117/12.383495
|View full text |Cite
|
Sign up to set email alerts
|

<title>Structure of coastal dunes: observations from ground penetrating radar (GPR) surveys</title>

Abstract: The structure of coastal dunes from three different sites within Wales, UK, have been investigated using ground penetrating radar (GPR), revealing the internal structure of the dunes. GPR provides a unique insight into the internal structure of coastal dunes that cannot be achieved by any other non-destructive or geophysical technique. The profiles presented show results from surveys investigating sand thickness and distribution, and dune structure and statigraphy. Surveys at Towyn Warren map the base of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…As a wave-based technique, GPR provides high-resolution structural information that cannot be obtained by other EM methods. Most reflectors in a given radar section can be interpreted as being caused by waves reflecting from discontinuities in the primary depositional fabric or interfaces within and between sedimentary structures including cross-stratified beds and erosional surfaces (Bailey and Bristow, 2000), in addition to hydrologic interfaces such as the water table and freshwater/saltwater interfaces beneath the shoreline.…”
Section: Methodsmentioning
confidence: 99%
“…As a wave-based technique, GPR provides high-resolution structural information that cannot be obtained by other EM methods. Most reflectors in a given radar section can be interpreted as being caused by waves reflecting from discontinuities in the primary depositional fabric or interfaces within and between sedimentary structures including cross-stratified beds and erosional surfaces (Bailey and Bristow, 2000), in addition to hydrologic interfaces such as the water table and freshwater/saltwater interfaces beneath the shoreline.…”
Section: Methodsmentioning
confidence: 99%
“…Vertical resolution of a radar reflection profile increases as frequency increases as well [20][21][22]; this has important implications for its sedimentological interpretation, as it will determine the scale of sedimentary structure that can be observed [23]. GPR, in fact, can easily detect the internal structure of detritic deposits due to the occurrence of stratification or lamination as well as to grain size change (see, for instance, [24]).…”
Section: Methodsmentioning
confidence: 99%
“…The application of GIS to analysing changes in dune morphology and volume was reported by Andrews et al (2002) and Woolard and Colby (2002) illustrated the application of LiDAR to the same issue while Shanmugam et al (2003) reported the use of different remote sensing techniques in mapping dune ecosystems and vegetation patterns on dunes. The internal structure of dunes was investigated using ground penetrating radar by Bailey and Bristow (2000) and Bristow et al (2000). Holocene dune development remains a popular theme with a number of investigations in a variety of settings (Murillo de Nava and Gorsline, 2000;Goudie et al, 2000;Orford et al, 2000;Sanderson et al, 2000;Hesp, 2001;Borówka and Rotnicki, 2001;Clemmensen et al, 2001;Wilson et al, 2001;Wilson, 2002;Mastronuzzi and Sanso, 2002;Regnauld and Louboutin, 2002;Arbogast et al, 2002;Murray-Wallace et al, 2002 andOrford et al, 2003).…”
Section: Dunesmentioning
confidence: 99%